Events which did not take place. Ukrainian Philosophical Congress - колегія, Редакційна (Filosofska Dumka, 2017)
Information devoted to certain philosophical events notable by the fact that they did not take place. The question is in the competitions for the best achievements of young researchers in the field of philosophy, as well as in the All-Ukrainian Philosophical Congress. The long-term absence of these events, in spite of all their urgency, evidences for the defects of our intellectual life. Firstly, the understanding of this situation has impelled at last to announce a competition for obtaining Prizes in philosophy of 2016 and National competition in the field of philosophical translation in two subnominations (in translations of classical and modern philosophical literature). Secondly, the working group of the H.S. Skovoroda Institute of Philosophy of NAS of Ukraine appeals to philosophical community with preliminary propositions concerning the preparation of All-Ukrainian Philosophical Congress “Philosophy for the Future of Ukraine”.